Psychological Approaches in 21st Century Learning to Improve the Quality of SDG Education Point 4 in Bibliometric Studies - Indri Hapsari Khansa; Rahmatta Thoriq Lintangesukmanjaya; Dwikoranto Dwikoranto; Daniel Hakim (Journal of Law and Bibliometrics Studies, 2026)
Objective: The research aims to comprehensively understand the various psychological challenges in learning in the 21st century education era. This approach not only helps identify dominant research themes, but also uncovers research areas that are still rarely studied, so that it can provide a stronger basis for formulating further research directions in the field of learning psychology that supports the transformation of quality education SDG point 4.  Method: This research uses a literature study approach with bibliometric analysis methods to map the development of research related to psychological aspects in 21st century learning. Scopus data was obtained from 106 documents in 2016-2016 which were analyzed using the PRISMA design to determine the bibliometric distribution.  Results:  Research trends regarding psychological approaches to learning continue to increase in supporting 21st century education. Bibliometric analysis indicates that themes such as learning motivation, self-regulation, learner engagement, and experience-based learning are the main focus in current studies. Research contributions are also dominated by several countries that are actively developing pedagogical innovations to answer modern learning challenges.  Novelty: The findings of this research indicate that the integration of psychological aspects in learning design is very important to improve the quality of education in the 21st century. Educators need to implement a learning model that is student-centered and supports balanced cognitive, emotional and social development. In addition, the results of this research can be a basis for developing educational policies that pay more attention to psychological well-being in the learning process.